Digital Games as a Tool for Gender Education: The Position of Educational Games and Independent Works in the Gaming Market - Veronika Šašalová; Miroslav Macák (Communication Today, 2025)
Prior feminist studies in the field of digital education focus primarily on the need to retrain teachers and the need to attract women to programming. Digital games have been a part of both formal and informal education processes for several decades. Despite their longstanding prominence, the potential for gender education has not yet been fully explored. The paper focuses on specific games and uses content analysis to focus on the interactive, narrative and audiovisual components of digital games and on individual motifs or mechanics that are associated with appropriate feminist themes. The main aim of the article is to showcase the abilities and limits of educational digital games created by independent developers to teach players within the gaming community about topics of sexuality. The text also shows how individual games can help in the field of gender education. At the same time, by examining the game market, we estimate what possibilities independent educational games have for reaching audiences in gaming culture.